2022
DOI: 10.1186/s12912-022-00823-3
|View full text |Cite
|
Sign up to set email alerts
|

Staff experience of a Canadian long-term care home during a COVID-19 outbreak: a qualitative study

Abstract: Background COVID-19 has significant impact on long-term care (LTC) residents and staff. The purpose of this paper is to report the data gathered during a COVID-19 outbreak in a Canadian LTC home regarding staff experiences, challenges, and needs, to offer lessons learned and implications. Methods A total of 30 staff from multiple disciplines participated in the study, including nurses, care workers, recreational staff, and a unit clerk. Focus group… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 25 publications
4
30
0
Order By: Relevance
“…Despite the enormous burden of distress and potentially traumatic events experienced by HCWs in LTC homes, some studies (Blanco-Donoso et al, 2021; Dohmen et al, 2022) highlighted the positive feelings experienced by HCWs including a sense of duty and commitment to care and gratification and fulfillment working during the crisis and how their work contributed to the greater good of society. For instance, participants reported feelings of pride, satisfaction in helping others (Hung et al, 2022) and professional fulfillment in providing care to residents during the pandemic. HCWs who had more social support at work experienced higher levels of professional satisfaction despite the demanding work conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the enormous burden of distress and potentially traumatic events experienced by HCWs in LTC homes, some studies (Blanco-Donoso et al, 2021; Dohmen et al, 2022) highlighted the positive feelings experienced by HCWs including a sense of duty and commitment to care and gratification and fulfillment working during the crisis and how their work contributed to the greater good of society. For instance, participants reported feelings of pride, satisfaction in helping others (Hung et al, 2022) and professional fulfillment in providing care to residents during the pandemic. HCWs who had more social support at work experienced higher levels of professional satisfaction despite the demanding work conditions.…”
Section: Resultsmentioning
confidence: 99%
“…22 Other studies have also highlighted the psychological toll of the pandemic on staff, including increased work-related stress, fear of infection, and fear of transmission to family and friends. 23 , 24 , 25 Despite these outcomes, not all staff who reported serious effect of COVID-19 also reported the need for additional support. This may indicate staff hesitancy to ask for support when needed; in offering interventions to support workers, it may be necessary to overcome this perception.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the current situation around COVID-19 may have accelerated the presence of conditions for establishing workplace learning, because the pandemic was seen as an urgent, exceptional situation. For example, Hung and colleagues showed that there was a sense of increased solidarity between nursing staff to provide the best, safest care possible while also looking out for one another [ 37 ]. They also reported an increased level of teamwork as crucial to the nurses’ success.…”
Section: Discussionmentioning
confidence: 99%